Safety, clinical and laboratory characteristics of donors with thalassemia minor in living donor kidney transplant: a case series - Nhan Hieu Dinh (BMC, 2021)
Abstract Background Due to the increasing demand for kidney transplants, sometimes donors with underlying medical conditions can be considered for living kidney donor transplant. Thalassemia is amongst the most common inherited disorders of hemoglobin globally, which is not restricted as an exclusion criterion. However, there is currently no study examine the safety and characteristics of kidney donors with thalassemia minor. Methods All eligible live kidney donors between 2016 and 2019 with thalassemia minor at a tertiary hospital were recruited. Baseline characteristics, clinical and laboratory outcomes were investigated. Results Fifteen donors (11 women, 55.5 ± 15.0 year-old) were included with a follow-up duration of 2 (1-4) years since operation. The most prevalent gene mutation among participants was DEL-SEA. No clinical manifestations of anemia were seen but 10 participants had mild anemia diagnosed from blood tests. Cardiovascular, liver and renal function were normal before nephrectomy. Until now, all donors are alive and maintain overall good health. Anemia condition is not affected, and the post-donation eGFR = 71.04 ± 11.54 mL/min/1.73m2 is comparable to outcomes of healthy donors reported in previous studies. Two donors are at risk of proteinuria at 1-year post-transplant with A/C ratio > 30 mg/g. Conclusions Thalassemia minor individuals who are non-transfusion-dependent, without anemia clinical manifestations and have no contraindications to kidney donation are safe to be donors in short-term. An eGFR of at least 80 mL/min/1.73m2 should be considered to avoid low post-donation eGFR, and awareness should be raised on thalassemia donors with even mild albuminuria. Nephrectomy does not worsen thalassemia.